Determinants of Village Savings and Loans Association membership and savings amounts in Awutu Senya West District of Ghana - Aaron Alesane; Kamaldeen Yussif; Benjamin Tetteh Anang (Cogent Economics & Finance, 2019)
At the macro level, savings mobilization plays an important role in economic growth and development whilst at the micro household level it plays a critical role in production, consumption and investment decisions. However, savings mobilization in many developing countries remains low which calls for further research and insight into the savings behaviour of the poor and ways to encourage rural savings. This study therefore investigates the factors influencing the decision to join Village Savings and Loans Association (VSLA) in Awutu Senya West District of Ghana and the resulting amounts saved. Using a cross-sectional design and a linear regression with endogenous treatment-effects model, the study indicated that the propensity to join VSLA was positively related to household size and respondent being male but was negatively associated with respondent's age and educational status. Also, absolute amount saved increased with respondent's age, education and amount of current loan. In general, absolute savings amounts were very low. The estimated average treatment effect of VSLA membership on savings indicated that belonging to a VSLA increased the savings of members by GH¢ 268. Thus, VSLAs can be used as channels to deepen financial inclusion and savings mobilization among the rural poor to promote the growth of the rural economy.
Keywords: 330; informal financial sector; rural savings mobilization; microfinance; Village Savings and Loans association; Awutu Senya West District